IDEOLOGICAL PERSPECTIVES ON EXTERNAL DEBT AND ADJUSTMENT PROGRAMMES - Dantani, Umar; Kalgo, Abubakar Musa (IJRDO - Journal of Social Science and Humanities Research, 2018)
This paper examines the ideological debate between state intervention model versus free market economy. The methodology of this paper is based on content analysis and qualitative techniques. The paper argues that due to the failure of the free market economy to address economic inequalities some scholars within the classical liberals reversed their doctrine of free market economy to state intervention. The paper also argues that state intervention in the management of the economy is necessary in order to provide social services and regulate capitalism. There is no doubt state intervention has provided social services to the people however the model was confronted with corruption among state officials and complex activities that resulted to inefficiency. The paper maintains that the wave of globalization that requires the adoption of adjustment programmes as conditionality for external loan facility has made most of the third world nations to abandon state intervention model to free market economy where the forces of demand and supply regulate the economy. The paper concludes that despite the criticisms of free market economy by many scholars as exploitative liberal democracy one of the principles of free market economy has triumphed over all other ideologies in the world.